PENGARUH LABEL NEGATIF TERHADAP PEMULUNG DI MASYARAKAT (STUDI KOTA TANJUNGPINANG) - Lisa Ira; Lidya Erdawati; Heni Widiyani (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
Abstract Some people's perspectives see waste pickers in a negative light, assuming that they interfere with the safety and comfort of the community. This negative view arises as a result of irregularities committed by unscrupulous scavengers, for example by taking goods that have not been disposed of by their owners. In this case, the stigma towards the negative label of scavengers that exists in the community has a direct influence on the activities carried out by scavengers, especially on scavengers who usually go around both on the streets and around people's housing. This research was conducted to answer and examine how the influence of negative labeling in society on waste pickers in Tanjungpinang City. The research method used in this research is qualitative research with descriptive methods with the data collection techniques used in this research are observation and interviews. As an analysis knife in this research, two theories are used as references, namely labeling theory and stigma theory. The results show that negative labeling of waste pickers affects other waste pickers who do not commit irregularities, honest waste pickers who work only to make a living for their families are affected by the label. This means that the label creates a stigma in the community towards waste pickers.